The Lives of Papa Guibernas narrative variations in a millenarian life-history - Paclibar, Ralph James
Reverend Maximino Guibernas is the late founder of New Israel Moncadistas, a religious movement having its focus of activities in New Israel, Makilala, North Cotabato. His Christ-like life-history is an important pillars in the "theology" of the millenarian believers. This study looks into the variations of the life-history narratives that the believers transmit to new generations of believers. This study gathers sample-collections of these Papa Guibernas narratives circulating among old and new members of the place. By describing the changes and continuities, in details and structure, of the sampled narratives, this study opens an important preliminary step in local community social science research along the theme of "memetics). The gathered narratives about the life history of Papa Guibernas were analyzed to determine the various themes and figurations present. Some themas exist commonly throughout all the narratives and these common themes were subsequently scrutinized to analyze and identify the discrepancies between them in the various narratives. This research can be considered as an exploratory study on the theory of memetics-the replication of ideas from one individual to another -- whereby the narratives collected provide a very good example of meme replication and as a basis for future memetic studies.